Sintesis Zeolit 4a Dari Fly Ash Sawit Dengan Variasi Perbandingan Volume Reaktan Dan Kecepatan Pengadukan - R, Yolanda.; Yelmida, Yelmida; Zahrina, Zahrina (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Zeolit defines as Alumina Silika Crystal which have structure 3 dimension that formed by silica and alumina tetrahedral with three voids dimension content with balanced metal load ions of zeolit bone and water molecule that could move freely. Water content in zeolit’s cavity at least 10 – 50%. If it hidrated, cations that place in that cavity will be cover by water molecule and have unstabilize or release easly as it property. Zeolit 4A is shynthetic Zeolit which have load as cation exchange is Na. To produce zeolit 4A, we need ratio of Na2SiO3/ NaAlO2 = ½. Ratio of Si Oxide and Al Oxide in basic material and temperature reaction will be influence type of zeolit that produced. Shyntesys of zeolit 4A with waste material from a process as feed, which is include some procedure: preparation or pretreatment for feed, forming and gel saving, crystalization. Separation, washing and drying. Purpose of this research to get advantage from fly ash as source of silica as feed for zeolit 4A and learn the influnce of ratio of reactan volume (pottasium aluminat and pottasium sillicate) and rate of agitation. Shyntesys of zeolit 4A doing by mix pottasium silicate and poyttasium aluminat with variation of volume at 40:60 and 60:40 ml/ml and rate of agitation at 200, 250, 300, 350 and 400 rpm until it formed as gel. Then the gel will be heated in oven for 8 hours and washed until the pH netral. After washing process, gel will be heated at 120 oC for 3 hours. Synthesize product analyzed with IR Spectroscopy and Xray Difraction. The best result was got in variation volume at 60/40 and rate of agitation at 400 rpm Keywords : Xray Difraction, Fly ash, Synthesize, IR Spectroscopy, Zeolit 4A